(untitled) (Solukhumbu Multiple Campus Research Journal, 2024)
The primary aim of this study is to analyze the relationship between teacher motivation and their teaching performance, focusing on how motivational levels among teachers affect educational outcomes. A mixed-methods approach was employed, utilizing purposive sampling to select a population of 24 secondary-level teachers from four private schools. Data collection was conducted through a pre-formulated questionnaire containing both closed and open-ended questions. Findings revealed that 92% of the teachers exhibited low motivation, which negatively impacted student engagement and academic performance. Motivated teachers demonstrated greater enthusiasm and commitment, essential for fostering positive learning environments, particularly in resource-limited rural areas. Challenges faced by teachers included insufficient organizational support, lack of insurance, medical benefits, retirement plans, and promotion opportunities. Only 12.5% had access to professional development opportunities, leading to stagnation in teaching practices and low morale. Consequently, 75% of students showed reduced participation and lower academic results due to disengaged teachers. Private schools should offer competitive salaries, benefits, career growth, professional development, recognition, and a supportive environment to motivate teachers, enhance performance, and improve the quality of education. Implementing these strategies is vital for enhancing teacher motivation and ultimately improving the quality of education for students in private schools within Solukhumbu district.